2000
DOI: 10.1097/00000658-200010000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After Different Types of Solid Organ Transplantation

Abstract: ObjectiveTo describe functional health and health-related quality of life (QOL) before and after transplantation; to compare and contrast outcomes among liver, heart, lung, and kidney transplant patients, and compare these outcomes with selected norms; and to explore whether physiologic performance, demographics, and other clinical variables are predictors of posttransplantation overall subjective QOL. Summary Background DataThere is increasing demand for outcomes analysis, including health-related QOL, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
1
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(182 citation statements)
references
References 16 publications
(19 reference statements)
12
155
1
10
Order By: Relevance
“…13 The somatic symptoms that we found (excess appetite, trembling, and headaches) can be considered to be the side effects of immunosuppressive drugs. It was reported that deaths related to immunosuppressive treatments from chronic rejection, opportunist infections, and lymphoma represent 40% of late mortality after LT. 23 Pinson et al 24 are convinced that results of the QOL can be used similarly to the rate of rejection to determine immunosuppression regimen or other strategies of patient management. During recent years, a dramatic improvement has been achieved in the area of electronic data transmission.…”
Section: Discussionmentioning
confidence: 99%
“…13 The somatic symptoms that we found (excess appetite, trembling, and headaches) can be considered to be the side effects of immunosuppressive drugs. It was reported that deaths related to immunosuppressive treatments from chronic rejection, opportunist infections, and lymphoma represent 40% of late mortality after LT. 23 Pinson et al 24 are convinced that results of the QOL can be used similarly to the rate of rejection to determine immunosuppression regimen or other strategies of patient management. During recent years, a dramatic improvement has been achieved in the area of electronic data transmission.…”
Section: Discussionmentioning
confidence: 99%
“…7 Desai et al's study 8 in this issue of Liver Transplantation provides valuable cross-sectional information on the quality of life of patients at least 10 years (and up to 30 years) after they underwent liver transplantation. Their patient population consists of 57 residents in the United Kingdom who received a liver transplant between 1968 and 1994 and completed a mail survey asking about their quality of life.…”
Section: See Article On Page 1473mentioning
confidence: 99%
“…Patients report that HRQoL is improved immediately after transplantation, and they further report that gains are sustained. [201][202][203][204][205][206][207][208][209] However, these findings may be influenced by a transplantation specific bias: there may be personal, familial, peer, and provider pressures for the patient to be convinced that the risks and costs undertaken to undergo this irreversible procedure were worthwhile. Due to the incomparable nature of HRQoL and survival, adjustments for patients with early mortality, a stubbornly persistent 10%-15% of all recipients within 6 months of transplantation 1,100 and more than 20% in selected groups, 1 cannot be done.…”
Section: Quality Of Lifementioning
confidence: 99%
“…Due to the incomparable nature of HRQoL and survival, adjustments for patients with early mortality, a stubbornly persistent 10%-15% of all recipients within 6 months of transplantation 1,100 and more than 20% in selected groups, 1 cannot be done. Application of positive findings in the papers reviewed [201][202][203][204][205][206][207][208][209] is limited in the context of modern lung transplantation for COPD. The studies were performed over several decades; studied patients and earlier surgical methods may or may not be comparable to current patients contemplating or awaiting lung transplantation and contemporary techniques, respectively.…”
Section: Quality Of Lifementioning
confidence: 99%